2018
DOI: 10.3390/en11061470
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism Reduction for Ozone-Enhanced CH4/Air Combustion by a Combination of Directed Relation Graph with Error Propagation, Sensitivity Analysis and Quasi-Steady State Assumption

Abstract: In this study, an 18-steps, 22-species reduced global mechanism for ozone-enhanced CH 4 /air combustion processes was derived by coupling GRI-Mech 3.0 and a sub-mechanism for ozone decomposition. Three methods, namely, direct relation graphics with error propagation, (DRGRP), sensitivity analysis (SA), and quasi-steady-state assumption (QSSA), were used to downsize the detailed mechanism to the global mechanism. The verification of the accuracy of the skeletal mechanism in predicting the laminar flame speeds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The sensitivity coefficients, λ i,j , are used to identify the reactions that significantly impact the production of desired species. It can be estimated using Equation ( 8) 29 :…”
Section: Fssa Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity coefficients, λ i,j , are used to identify the reactions that significantly impact the production of desired species. It can be estimated using Equation ( 8) 29 :…”
Section: Fssa Methodsmentioning
confidence: 99%
“…The sensitivity coefficients, λ i,j , are used to identify the reactions that significantly impact the production of desired species. It can be estimated using Equation () 29 : λij=lnCjlnri=CjririCj\begin{equation}{\lambda _{ij}} = \frac{{\ln {C_j}}}{{\ln {r_i}}} = \frac{{\partial {C_j}}}{{\partial {r_i}}}\frac{{{r_i}}}{{{C_j}}}\end{equation} C j is the concentration of species, j and r i are the reaction rate of i th reaction. Reactions with a significant value of λ ij are likely to produce highly reactive radicals and enhance the overall reactivity and vice versa.…”
Section: Development Details Kinetic and Model Reductionmentioning
confidence: 99%
“…Finally, they validated this mechanism by several experiments and found that the developed skeletal mechanism could reproduce the results from the detailed mechanism. The DRGASA method was also confirmed as a successful tool for mechanism reduction by Liu et al [ 29 ]. Skeletal mechanisms developed using the reduction method should only be used for those applications and boundary conditions for which they were created, as discussed by Liu et al [ 29 ] and Zhao et al [ 30 ].…”
Section: Introductionmentioning
confidence: 91%
“…The DRGASA method was also confirmed as a successful tool for mechanism reduction by Liu et al [ 29 ]. Skeletal mechanisms developed using the reduction method should only be used for those applications and boundary conditions for which they were created, as discussed by Liu et al [ 29 ] and Zhao et al [ 30 ]. However, it often happens that a skeletal mechanism developed on the basis of simple applications can be used for more complex simulations and still has satisfactory accuracy.…”
Section: Introductionmentioning
confidence: 91%